Preferential Production and Transport of Grass-Derived Pyrogenic Carbon in NE-Australian Savanna Ecosystems - Saiz, Gustavo; Goodrick, Iain; Wurster, Christopher; Nelson, Paul N.; Wynn, Jonathan; Bird, Michael (Frontiers in Earth Science, 2018)
Understanding the main factors driving fire regimes in grasslands and savannas is critical to better manage their biodiversity and functions. Moreover, improving our knowledge on pyrogenic carbon (PyC) dynamics, including formation, transport and deposition, is fundamental to better understand a significant slow-cycling component of the global carbon cycle, particularly as these ecosystems account for a substantial proportion of the area globally burnt. However, a thorough assessment of past fire regimes in grass-dominated ecosystems is problematic due to challenges in interpreting the charcoal record of sediments. It is therefore critical to adopt appropriate sampling and analytical methods to allow the acquisition of reliable data and information on savanna fire dynamics. This study uses hydrogen pyrolysis (HyPy) to quantify PyC abundance and stable isotope composition (δ13C) in recent sediments across 38 micro-catchments covering a wide range of mixed C3/C4 vegetation in north Queensland, Australia. We exploited the contrasting δ13C values of grasses (i.e. C4; δ13C >-15‰) and woody vegetation (i.e. C3; δ13C <-24‰) to assess the preferential production and transport of grass-derived PyC in savanna ecosystems. Analyses were conducted on bulk and size-fractionated samples to determine the fractions into which PyC preferentially accumulates. Our data show that the δ13C value of PyC in the sediments is decoupled from the δ13C value of total organic carbon, which suggests that a significant component of PyC may be derived from incomplete grass combustion, even when the proportion of C4 grass biomass in the catchment was relatively small. Furthermore, we conducted 16 experimental burns that indicate that there is a comminution of PyC produced in-situ to smaller particles, which facilitates the transport of this material, potentially affecting its preservation potential. Savanna fires preferentially burn the grass understory rather than large trees, leading to a bias toward the finer C4–derived PyC in the sedimentary record. This in turn, provides further evidence for the preferential production and transport of C4-derived PyC in mixed ecosystems where grass and woody vegetation coexist. Moreover, our isotopic approach provides independent validation of findings derived from conventional charcoal counting techniques concerning the appropriateness of adopting a relatively small particle size threshold.